Does long-term use of proton pump inhibitors cause hypomagnesaemia in Japanese outpatients? - Takeda, Yasuhito (BMJ Open Gastroenterol, 2015)
AIM: Hypomagnesaemia has been reported associated with long-term proton pump inhibitor (PPI) treatment. However, there have been no studies in Japanese patients. We therefore assessed the effects of long-term PPI use on serum magnesium concentrations in Japanese patients. METHODS: Data from 481 outpatients who visited our centre in October and November 2011 were reviewed to determine their underlying diseases, oral medications, including PPIs, and serum magnesium concentrations. The association between PPI use and serum Mg concentrations was assessed by multiple linear regression analysis. RESULTS: Serum magnesium concentrations were significantly lower in PPI users (n=199) than in PPI non-users (n=282; 1.86±0.21 vs 1.91±0.19 mg/dL, p<0.01). Multiple linear regression analysis showed that the presence or absence of cirrhosis and PPI use was a significant predictor of magnesium concentration. In evaluating magnesium concentrations among PPI users and non-users with and without cirrhosis, we found that mean serum magnesium concentrations in patients with cirrhosis were significantly lower in PPI users than non-users (1.78±0.22 vs 1.87±0.22 mg/dL, p=0.03). CONCLUSIONS: Outpatients receiving long-term PPI treatment had significantly lower serum magnesium concentrations than those not treated with PPI. To the best of our knowledge, this study is the first to show hypomagnesaemia in Japanese patients with cirrhosis receiving long-term PPI treatment.